1974
DOI: 10.1007/bf02512392
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory responses by the heterotrophic marine dinoflagellateCrypthecodinium cohnii

Abstract: Chemosensory responses by the colorles inshore marine dinoflagellateCrypthecodinium cohnii were observed in quadrant-divided Petri plates containing an agar layer + liquid overlay. A suspension of organisms in salt solution was poured onto this and allowed to stand 3 hr. A differential tendency of the cells to become firmly attached or embedded in the substratum was observed when various substances were incorporated in the gel. A positive response (tendency to attach) occurred with: α-L-fucose, dimethyl-β-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…These results are also in accordance with the growth and predation experiments. Crypthecodinium cohnii has previously been shown to be attracted to a variety of chemical compounds, such as sugars and amino acids (Hauser et al 1975, Spero 1985, and a more detailed study of the chemosensory attractants of our isolate of C. cohnii is under way.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results are also in accordance with the growth and predation experiments. Crypthecodinium cohnii has previously been shown to be attracted to a variety of chemical compounds, such as sugars and amino acids (Hauser et al 1975, Spero 1985, and a more detailed study of the chemosensory attractants of our isolate of C. cohnii is under way.…”
Section: Discussionmentioning
confidence: 97%
“…(Ucko et al 1989). It has, however, recently been identified as Crypthecodinium cohnii, a heterotrophic dinoflagellate that has been studied in some detail (Gold & Baren 1966, Hauser et al 1975, Tuttle & Loeblich 1975, Beam & Himes 1982. This dinoflagellate was found to grow only on the cells of the red microalga Porphyridium sp., but not on other microalgae or on a medium alone (Ucko et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing Ditylum brightwelli with Dunaliella tertiolecta as food for Oblea rotunda, Strom & Buskey (1993) noted that the non-motile diatom consistently supported higher rates of growth and grazing than the motile flagellate. In addition to prey size (Hansen 1992) and chemosensory signals (Hauser et al 1975, Spero 1985, Buskey 1997, feeding selectivity among pallium-feeding heterotrophic dinoflagellates may thus partly be ascribed to prey motility as an active defence mechanism. The quantification of motility as an effective defence mechanism presented here, however, may be variable and may mainly depend on the swimming activity of the F. japonica cells, which in turn depend on both environmental factors and physiological conditions (Khan et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…5) and to a solution of a single amino acid (Fig 6), indicating that it is capable of remote perception of chemosensory signals associated with the phytoplankton it feeds on. Several previous studies have demonstrated chemosensory capabilities in heterotrophic dinoflagellates and indicated a potential role of free amino acids in chemosensory responses of heterotrophic dinoflagellates and other protozoa (Hauser et al 1975, Fitt 1985, Spero 1985. It seems likely that initial food choice by P. pellucidum is made by means of remotely detected chemosensory signals that stimulate the stereotypical pre-feeding behavior, More study is needed to determine the extent to which P. pellucidum can disting'uish between chemosensory signals associated with specific phytoplankton species.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotrophic dinoflagellates are an impol tant component of the mdrine miciozooplankton, often approaching 01 exceeding the abundance of planktonic ciliates (Burkill et a1 1993, Verity et a1 1993 and they have been shoxvn to be important grazels of diatoms (Hansen 1991, Tiselius & Kuylenstierna 1996 Due to morphological constraints ( 2 flagella compared to the numerous cilla of ciliates), heterotrophic dinoflagellates do not feed by filtering small particles from the water as some ciliates do (Fenchel 1986), instead they capture lndividual phytoplankton cells, sometimes nearly as large or larger than themselves, and either 'E-mail buskeyQutmsi.zo.utexas edu engulf the entire cell 01 t~ansfer body fluids of the captured cell into themselves by way of a palllum 01 a pedunclc (Gaines & Elbrachter 1987) Protopend~n~um pellucldum, the subject of this study, is a pallium feeder, and captures and digests single phytoplankton cells (or chains of cells) externally (Jacobson & Andelson 1986) Since larger phytoplankton cells are often less abundant than smaller-sized cells, heterotrophic dinoflagellates may not rely on random encounter with sultable food cells and therefore need some sensory modality to help them locate lndividual food particles After passing neai a potential food item, the P~o t o p e n d~n~u m spp circles around the food several times, usually bvithout contacting the cell (Jacobson & Anderson 1986) Thls behavior suggests that chemoreception is used to recognize and locate a potential food item Sev-era1 previous studies have demonstrated the role of chemoreception in the feeding behavior of heterotroph~c dinoflagellates (Hauser et al 1975, Spero 1985 and other protozoans (Levandowsky et al 1984, Verity 1988. Pallium feeding dinoflagellates of the genus Protoperidlnium have been previously shown to feed mainly on diatoms and dinoflagellates (Jacobson & Anderson 1986, Hansen 1991, Buskey et al 1994, Jeong & Latz 1994.…”
Section: Introductionmentioning
confidence: 99%